Chlorohexidine vs Herbal mouthwash effects on Salivary pH in Orthodontic patients - Israa R. Alkasso; Ghada A. Taqa; Sarmad S. Al qassar (University of Mosul, College of Dentistry, 2020)
Aims: This is a comparative study for two different mouthwashes (Herbal mouthwash vs Chlorohexidine mouthwash) on salivary pH in Orthodontic patients after acidogenic challenge by taking a carbonated beverage, compare it with baseline pH and determined the duration of action of mouthwash at which it will persist to protect teeth and oral mucosa from acidic pH. Materials and Methods: Twenty orthodontic patients were involved, 10 patients in each group, after taking one cup of carbonated beverage, they were gargling with one mouthwash for 5-10 seconds, then saliva pH was measuring in 0,5,10,15 minutes after gargling. Results: significant difference in pH after Pepsi drinking (5.47 ± 0.689) in compare with Baseline pH(6.65 ± 0.303), pH after Herbal Mouthwash at 0 time(6.79 ± 0.110), pH after 5mins(6.7 ± 0.115) from Herbal Mouthwash, pH after 10mins from Herbal Mouthwash (6.58 ± 0.139) and pH after 15mins from herbal mouthwash (6.53 ± 0.188), pH after zero min from gargling with Chlorohexidine Mouthwash )6.73 ± 0.231(, pH after 5mins from Chlorohexidine Mouthwash (6.59 ± 0.159), pH after 10mins from Chlorohexidine mouthwash (6.51 ± 0.166)and significant difference in pH after 15mins from Chlorohexidine mouthwash(6.37 ± 0.194) in compare with baseline pH at (P<0.05), while there were no significant differences between baseline salivary pH and the other pH measurement. Conclusion: Application both mouthwashes were elevated saliva pH directly higher than baseline pH and both are effective in enhancing saliva buffering capacity.